The Construction and Application of Process Evaluation in the Grade Evaluation of Pharmacology Experiment - Li, Hua; Liu, Lin; Li, Mao; Sun, Yuhong; Liu, Minghua (Indian Journal of Pharmaceutical Education and Research, 2025)
Pharmacology laboratory teaching includes basic animal handling, basic experiments, integrated experiments, designed experiments and scenario-based discussions between doctors and patients. The problems in the evaluation of pharmacology laboratory performance include the predominance of summative evaluation, a single index for laboratory performance assessment and weak teaching feedback. This paper aims to discuss the practice and significance of adding process evaluation to the evaluation system of pharmacology experiment teaching. Our university has initially established a process evaluation system, which has been fully applied in the pharmacology laboratory teaching of 896 students majoring in pharmacy, clinical pharmacy and traditional Chinese medicine. Process evaluation can not only deepen students' understanding and application of basic knowledge of pharmacology, but also stimulate students' innovative thinking and initiative and enthusiasm to participate in pharmacology experiments, laying the foundation for clinical drug use and new drug research, so as to build a new experimental teaching system and improve the quality of pharmacology experimental teaching.
Keywords: Grade Evaluation of Experiment; Pharmacology Experiment; Process Evaluation